«DUAL» FUNDUS OF EYE - G. M. Musina (Русский журнал детской неврологии)
Angiopathy of retinal vessels (retinal angiopathy) without another clinical manifestations often has rhinogenous etiology. This is facilitated by close anatomical and topographical connections between of orbits, sphenoid bone and paranasal sinuses, community of their circulatory, lymphatic system and innervation. The effects of anemia and stress on the retinal vessels are also important, it is also possible to be congenital vascular tortuosity. This open non-comparative, prospective short-term study involving 30 children aged from 1 year to 17 years was planned in order to clarify the possible causes of retinal angiopathy. Study investigations included: clinical neurological and laboratory diagnostic tests, including neuroimaging (computed tomography (CT) of brain). Follow-up was 6 months. Neurological causes of headaches were revealed in 8 (26.7%) children, deficient anemia (lack of iron, vitamin B12,folic acid) was verified in 4 (13.3%) children. In the vast majority of cases (18 or 60.0% of children) no pathology was revealed. Medical history and data of follow-up observation confirmed that most of the reflex-circulatory processes of the retinal vessels in our study developed in response to a respiratory infection or exacerbation of chronic rhinosinusitis